2022
DOI: 10.1177/08445621221089475
|View full text |Cite
|
Sign up to set email alerts
|

Birth Experiences, Breastfeeding, and the Mother-Child Relationship: Evidence from a Large Sample of Mothers

Abstract: Background It is a priority for public health professionals to improve global breastfeeding rates, which have remained low in Western countries for more than a decade. Few researchers have addressed how maternal perceptions of birth experiences affect infant feeding methods. Furthermore, mixed results have been shown in research regarding breastfeeding and mother-child bonding, and many studies are limited by small sample sizes, representing a need for further investigation. Purpose We aimed to examine the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 80 publications
0
12
0
1
Order By: Relevance
“…Davis and Sclafani (2022) reported that childbirth experience affects breastfeeding practice and duration. Negative birth experiences were identified as a risk factor for unsuccessful breastfeeding (Davis & Sclafani, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Davis and Sclafani (2022) reported that childbirth experience affects breastfeeding practice and duration. Negative birth experiences were identified as a risk factor for unsuccessful breastfeeding (Davis & Sclafani, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an integrative review of 26 studies by Coates et al (2019) revealed that a large minority of women had negative experiences with their C-section deliveries. Davis and Sclafani (2022) reported that childbirth experience affects breastfeeding practice and duration. Negative birth experiences were identified as a risk factor for unsuccessful breastfeeding (Davis & Sclafani, 2022).…”
Section: Disappointment For Undergoing a C-section Affects Breastfeed...mentioning
confidence: 99%
“…Eine Verletzung der Geburtsintegrität liegt vor, wenn die Frau sich nicht ernst genommen und nicht würdevoll behandelt fühlt, geburtshilfliche Entscheidungen ohne ihre ausdrückliche Zustimmung erfolgen [ 17 ] oder sie emotionale, verbale oder körperliche Grenzüberschreitungen bis hin zu Gewalt erfährt [ 18 , 19 ]. Mögliche Folgen von verletzter Integrität reichen von „Geburtstrauma“ mit posttraumatischen Stresssymptomen [ 20 , 21 ] über postpartale Depressionen [ 22 ] bis hin zu einer verringerten Bindung zwischen Mutter und Kind [ 23 ] und einer verminderten Wahrscheinlichkeit des Stillens [ 24 ].…”
Section: Introductionunclassified
“…Studies have found that a negative birth experience is associated with post-traumatic stress disorder, shorter periods of breastfeeding, and women choosing to have fewer subsequent children. [13][14][15] According to women who gave birth during the pandemic, the most intrusive change of procedure as a consequence of the pandemic was to restrict the access of a companion of choice for women during latent labor and the postpartum period. 11 A better understanding of how women perceived giving birth during the COVID-19 pandemic is critical for recognition of the importance of service user views and to build knowledge on how the impact of the restrictive measures influenced one of the most vulnerable and important periods of human life.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are of concern since negative childbirth experiences can severely impact the future health and well‐being of mothers and their newborns. Studies have found that a negative birth experience is associated with post‐traumatic stress disorder, shorter periods of breastfeeding, and women choosing to have fewer subsequent children 13–15 . According to women who gave birth during the pandemic, the most intrusive change of procedure as a consequence of the pandemic was to restrict the access of a companion of choice for women during latent labor and the postpartum period 11 …”
Section: Introductionmentioning
confidence: 99%